2009
DOI: 10.1002/rra.1308
|View full text |Cite
|
Sign up to set email alerts
|

The impact of small physical obstacles on the structure of freshwater fish assemblages

Abstract: Many studies have assessed the effects of large dams on fishes but few have examined the effects of small obstacles. Fishes were sampled and environmental variables were characterized at 28 sites in two Iberian streams, 14 located immediately downstream, upstream and between five small obstacles at river Muge and 14 at river Erra, considered as the reference stream. Multivariate analysis indicated that habitat variables like current velocity and depth, but not physicochemistry, were mainly responsible for site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Angermeier and Winston 1999;Gehrke et al 2002;Gillette et al 2005;Alexandre and Almeida 2010). This study showed that recolonization by small species (minnow and bullhead) could be rapid when access was provided to adjacent suitable habitat, showing the utility of simple assemblage surveys in documenting successful reconnection.…”
Section: Discussionmentioning
confidence: 78%
“…Angermeier and Winston 1999;Gehrke et al 2002;Gillette et al 2005;Alexandre and Almeida 2010). This study showed that recolonization by small species (minnow and bullhead) could be rapid when access was provided to adjacent suitable habitat, showing the utility of simple assemblage surveys in documenting successful reconnection.…”
Section: Discussionmentioning
confidence: 78%
“…Research has determined that inadequate passage solutions past micro-hydro schemes may have drastic consequences for fish species distribution and recruitment (e.g. Lucas et al, 2009;Alexandre and Almeida, 2010;Branco et al, 2011). The EA and recreational river users were well aware of the issues (raised by experts) and were concerned about the impact of the development on fish.…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…The DCI considers stream networks as branching lines of continuous habitat in which the absence of barriers yields a DCI value of 100. Alexandre and Almeida (2010) found changes in habitat caused by a series of perched crossings resulted in spatially segregated fish communities associated with each crossing so that upstream sites generally had fewer native species, and Nislow et al (2011) showed that species richness in stream segments upstream of perched crossings was reduced by as much as half the number of fishes occurring immediately downstream. Permeability of barriers is of concern because most stream obstacles do not completely thwart organism dispersal, that is, structures are considered semi-permeable.…”
Section: Introductionmentioning
confidence: 99%
“…As barriers are introduced, the number, placement, and permeability of barriers are considered so that the DCI value of a given system declines from 100, and the rate of decline can vary depending upon life history attributes of the stream organisms being considered (i.e., diadromous, moving between freshwater and marine systems; potamodromous, migrating within freshwater systems; Cote et al 2009). These examples illustrate the negative effects of fragmentation on the availability of habitat to fishes in stream networks and the capacity of semi-permeable barriers to mimic larger obstacles (e.g., impoundments; Winston et al 1991, Luttrell et al 1999 in disrupting dispersal pathways of fishes (Alexandre and Almeida 2010). For example, Norman et al (2009) found fish passage at road crossings that exhibited rapid drops in elevation at their outflow, commonly known as ''perching,'' was limited to periods of storm runoff when elevated discharges caused water levels to inundate perches.…”
Section: Introductionmentioning
confidence: 99%